New Asian regionalism : - Tran, Van Hoa (Palgrave Macmillan, 2003)
Increasing globalization and the expanding membership of the WTO have deeply affected all economies, developed and developing, worldwide. The impact is especially profound in the major countries in the Asian region that had achieved 'miracle' growth during the 1960s to mid-1990s and who also experienced serious economic downturn -- as a result of the 1997 Asia crisis, and the global economic slowdown since 2001, with uncertain times ahead -- and a short-term recovery has been seen only in a few countries, such as Korea. The emergence of a new Asian regionalism is an answer by the East and South-East Asian economies to deal effectively with these challenges and to improve trade and investment and create suitable welfare programmes. This collection of selected studies, by experts on major Asian countries, surveys, discusses and analyses the emerging problems and challenges facing these countries. The contributors propose solutions to enable better regional economic integration and more effective economic management in the future.